Znaczenie wizualizacji w prezentowaniu informacji w portalu korporacyjnym - Dudycz, Helena (The Importance of Visualization in the Enterprise Information Portal, 2007)
The paper focuses on an increasing use of visualization in the enterprise information portal (EIP). The first part briefly characterizes the reason for practice of visualization in solution to information systems. Then premises of implementation the enterprise portal are presented. The last part of the paper describes an exemplary use of visualization in the enterprise information portal.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (11); 2007; nr 1156, s. 20-28